Hardware development of auto focus microscope - Pebrianti, Dwi; Rosyati, Hamid; Faradila, Naim; Mohd Falfazli, Mat Jusof; Nurul Wahidah, Arshad; Luhur, Bayuaji (Universiti Malaysia Pahang, 2019)
The scientific instrument technology has growth faster than we all could imagine, there are many research team keeping their momentum in creating new innovation in scientific instrumentation technologies. The optical microscopes are still being used widely in the scientific research especially by researcher and medical practitioners. Manually deal with the microscope could make the user spend so much time to obtain the result of cleared image. It could cost hours to obtain the desire result. From this problem, this study proposes the development of hardware system for auto focused of an optical microscope. The proposed system consists of two stepper motors that will move the fine focus knob and the course focus knob on a microscope. The timing belts are being used as mounting between the stepper motor and the fine / course focus knob. The motor will moves step by step in same degree given from the command of a program. The motor are able to be controlled and it moves slowly to perform an auto focus task. Additionally, it is able to move in a small angle to find the proper exposure of the images scan. The hardware implementation of auto focus on the optical microscope has been tested and it worked perfectly. The result presented in this study shows that the proposed system is able to do auto focus in precise step which is 5° step.